Ionic composition and size characteristics of particles in the Lower Fraser Valley: Pacific 2001 Field Study - Anlauf, K; Li, S. M.; Leaitch, R; Brook, J.; Hayden, K.; Toom-Sauntry, D.; Wiebe, A (ATMOSPHERIC ENVIRONMENT, 2006)
The size distribution of aerosol chemical compositions was studied over a 2-week period in August 2001 at three locations (one urban and two semi-rural) in the Lower Fraser Valley (LFV) of British Columbia, Canada. The size distributions varied diurnally and were bimodal with a pronounced peak at about 0.3-0.55 mu m (accumulation mode) and SO42- 2-7 mu m (coarse mode). Generally, on an equivalent basis, the aerosol was dominated by SO42- (balanced by NH4+) in the accumulation mode range; SO42- often exhibited a diurnal variation that was primarily the result of fog deposition overnight and photochemical formation during the day. SO42- in the 3.1-6.2 mu m particles was mostly of marine origin. Most of the smaller particle SO42- was from anthropogenic sources and it is estimated that about 75% of the SO42- in the smaller particles were due to secondary processes. Oxalate, C2O42-, although at low concentrations (generally < 0.1 SO42- displayed a bi-modal size distribution, the accumulation mode being similar to SO42- and the coarse mode peaking at 4 1-1.8 mu m. Frequently at night, there was also a significant increase in NO3- in the accumulation mode that is attributed to the co-condensation of gas phase NH3 + HNO3 to form aerosol NO3- and the reactive uptake of N2O5 onto aerosols. In the coarse mode, the sea salt Cl- was frequently deficient relative to Na+ yet accompanied by a corresponding increase in NO3-; this was attributed to reaction of NO3- precursors (e.g., HNO3 and N2O5) with sea salt aerosol Cl-. (c) 2006 Elsevier Ltd. All rights reserved.